Clinical, epidemiological and evolution of severe nosocomial pneumonia in intensive care unit - Arroyo-Sánchez, Abel (2016)
Objective: To describe the clinical and epidemiological characteristics, evolution and to identify mortality factors associated in patients with SNP. Material and Methods: Descriptive study of a serie of cases of the Intensive Care Unit (ICU) of a General Hospital. Medical records of patients which received medical attention and who meet the selection criteria were reviewed. Results: Forty-one clinical records were evaluated. The average age was 69 old, predominantly male (68,3%). SNP was the reason of admission in 60.9% and 95.1% required mechanical ventilation. Hospital stay prior to diagnosis was 10 days, 65% of patients had some risk factor for multi resistence organisms, CPIS of entry was 9.3, cultures were positive in 39% of the cases and of these, 48.8% received proper antibiotic according to culture results. The days of stay in ICU were 20.6 days and 20 of the 41 medical records were for death patients. The clinical and epidemiological characteristics were similar between death and alive patients. An analysis of factors that could be associated with mortality SNP was made and it was found that for an age ≥ 70 years, the presence of any risk factor for multidrug resistence organism and control CPIS ≥ 6 were associated with higher mortality; while acquisition of the ICU was associated to lower mortality. Conclusions: The clinical, epidemiological characteristics and evolution of patients with SNP in our ICU were similar to those describe in the literature. Three factors associated with mortality in the ICU were identified.